Contamination Trends of Legacy and Emerging Compounds in Sediments from the Adriatic Sea - Combi, Tatiane <1987> (Alma Mater Studiorum - Università di Bologna, 2016)
Sediments are the final repositories for most pollutants, which can accumulate and remain in the sedimentary matrix for long periods of time and may accumulate through the food web, affecting marine biota, aquatic-dependent wildlife, and ultimately human health. Thus, a wide-ranging work monitoring different groups of contaminants in sediments is a key tool for a comprehensive understanding of contaminants behavior and identification of the overall environmental quality and possible threatens to the whole marine ecosystem. POPs, among which PCBs and DDTs rank first, polycyclic aromatic hyrocarbons (PAHs), and selected groups contaminants of emerging concern (CECs) (fragrances, UV filters, endocrine disruptors) were the objective of this work. First, PCB congeners were analyzed in sediment cores and recent sediments along the north-south axis of the western Adriatic Sea. Chronological records of PCB concentrations and homologue patterns were assessed, supporting the reconstruction of PCBs fluxes and total inventories. Then, the spatial distribution and fate of selected legacy and emerging compounds were investigated in surface sediments sampled along the Adriatic mud-wedge and in deep-sea regions from the southern Adriatic basin, providing the first extensive dataset and also the evaluation of potential ecotoxicological risk of target emerging contaminants in sediments from the Adriatic Sea. Finally, the analyzes of selected legacy contaminants (PCBs, DDTs and PAHs) in sediment cores from coastal and deep-sea sediments from the Adriatic Sea supported the comparison between these two areas and further reinforces the hypothesis on the transfer of contaminants from contaminated areas in the northern Adriatic to the deep southern Adriatic basin. The present thesis is the summary of the work carried out in the last three year of the PhD program “Scienze ambientali: tutela e gestione delle risorse naturali” and contains three manuscripts (two under review and one in preparation), and the main conclusions regarding this PhD research project.